Advance Malignant Phyllodes Tumor with Active Bleeding in Children: A Rare Case - Dedy Hermansyah; Fernando Silalahi; Albiner Simarmata; Denny Rifsal Siregar (National Cancer Center - Dharmais Cancer Hospital, 2021)
Introduction: Phyllodes tumors are fibroepithelial breast lesions that are uncommon in women and rare among children. Due to scarcity, there are only a few large pediatric phyllodes tumor series. Current guidelines do not differentiate treatment recommendations between children and adults.Case Presentation: A 12-year-old girl presented with a lump in her right breast which grew rapidly within a month. On physical examination, we found a mass on the right breast sized ± 10 x 10 cm; the lump was fragile and bled easily. The patient’s condition was getting worse and worse. Due to this deterioration, we performed a mastectomy immediately.Conclusions: The incidence of malignant phyllodes tumor in children is very rare and required prompt treatment in emergency cases.